Maksimalisasi Keuntungan Pada Usaha Dagang Kue Tradisional Bu Ani Menggunakan Metode Simpleks dan TORA - Sutiara Citra Novrianti; Silvia Dwi Putri; Yasmin Risha Fadhilah; Suvriadi Panggabean (Lembaga Pengembangan Kinerja Dosen, 2024)
The traditional cake trading business is a type of business in the culinary sector that sells food in the form of cakes with certain cultural characteristics, both on a small scale (MSMEs) and on a large scale (parties). To be able to maintain the sustainability and development of the traditional cake trading business, a way is needed to distribute raw materials and make a profit. Therefore, an appropriate technique or method is very necessary in managing the raw materials for the products to be produced. In this research, the simplex method was used and by utilizing current AI technology, namely the use of TORA tools and comparing it with manual calculations to predict the maximum profit that can be obtained from each production by traditional cake traders within a period of one day, so as to have an accurate calculation estimate. . The result of calculating the maximum profit in a day is IDR 2,950.00.